Quantifying the relationship between internal and external work in team sports: development of a novel training efficiency index - Delaney, J. A.; Duthie, G. M.; Thornton, H. R.; Pyne, D. B. (Science and Medicine in Football, 2018)
Objective: To establish whether a simple integration of selected internal and external training load (TL) metrics is useful for tracking and assessing training outcomes during team-sport training. Methods: Internal [heart rate training impulse (HR-TRIMP), session rating of perceived exertion (sRPE-TL)] and selected external (global positioning systems; GPS) metrics were monitored over seven weeks in 38 professional male rugby league players. Relationships between internal and external measures of TL were determined, and an integrated novel training efficiency index (TEI) was established. Changes in TEI were compared to changes in both running performance (1.2 km shuttle test) and external TL completed. Results: Moderate to almost perfect correlations (r = 0.35-0.96; ±~0.02; range ± 90% confidence limits) were observed between external TL and each measure of internal TL. The integration of HR-TRIMP and external TL measures incorporating both body mass and acceleration/deceleration were the most appropriate variables for calculating TEI, exhibiting moderate (ES= 0.87-0.89; ±~0.15) and small (ES = 0.29-0.33; ±~0.07) relationships with changes in running performance and completed external TL respectively. Conclusions: Combination of the TEI and an athlete monitoring system should reveal useful information for continuous monitoring of team-sport athletes over several weeks.